Pakistan's Dependence on China for the Second Phase of CPEC Cooperation in 2020-2021 - Bangkur, Agnes Deandra (Jurnal Politik, 2024)
The China-Pakistan Economic Corridor (CPEC), an important component of China's Belt and Road Initiative (BRI), has been a landmark project since its inception in 2015. The project aims to develop a modern Silk Road that increases China's economic reach by capitalizing on Pakistan's strategic geographic position. However, this cooperation has raised concerns about Pakistan's growing dependence on China, posing a risk to the country's long-term stability. Artiel examines the implications of Pakistan's dependence on China within the framework of Dependency Theory, particularly in the continuation of the second phase of CPEC cooperation. By analyzing a wide range of literature and official documents, including statements by the Prime Minister of Pakistan, data from relevant agencies, and information from the official CPEC website, the research reveals the complex dynamics of this relationship. The findings reveal that while Pakistan views its proximity to China as a way to achieve economic stability and safeguard national interests, these benefits also come with significant drawbacks. The research highlights the potential negative impacts of Chinese influence, including concerns regarding debt dependency and the broader implications of CPEC on Pakistan's sovereignty. The analysis founds that Pakistan's engagement with China, despite its economic motivations, may exacerbate the very vulnerabilities it seeks to address, raising questions about the long-term sustainability of this partnership.